Open Questions on Ion–Neutral Collisions and Coupling in the Lower Thermosphere–Ionosphere: Electrodynamics, Energetics and Dynamics - Theodoros E. Sarris; Stelios Tourgaidis; Dimitrios Baloukidis; Maxime Grandin; Astrid Maute; Robert F. Pfaff; Jeffrey Thayer; James Clemmons; Karl Laundal; Hanli Liu; Panagiotis Pirnaris; Noora Partamies; et al. (Surveys in Geophysics, 2026)
The Lower Thermosphere–Ionosphere (LTI) is the interface region between the Earth’s atmosphere and space. It is modulated by the energy and momentum deposition from the magnetosphere above and by the impacting waves from the lower atmosphere. The LTI region is defined by the co-existence and interaction of neutral and ionized species within the region’s electric and magnetic fields. This interplay results in unique and complex interactions between neutrals and plasmas, that are not fully understood and quantified to this date. In this paper we present an overview of some of the most important open questions related to ion/neutral coupling and the resulting collisional electrodynamics, collisional energetics and collisional dynamics processes. We outline the key reasons for addressing these questions, and highlight methodologies that can lead to their closure in the upcoming years.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Earth's rotation and Earth-Moon distance in the Devonian derived from multiple geological records - Christian Zeeden; Jacques Laskar; David De Vleeschouwer; Damien Pas; Anne-Christine Da Silva (Earth and Planetary Science Letters, 2023)